Sweet Potato Cream Soup as an Alternative Healthy Breakfast Menu - Ai Mahmudatussa'adah; Tati Setiawati; Sudewi; Ade Juwaedah (Universitas Djuanda, 2021)
Breakfast is an important thing for everyone. Breakfast requires a complete nutritional composition. Cream of sweet potato soup is an alternative to a proper healthy meal. Sweet potato (Ipomoea batatas L) contains carbohydrates, vitamins, minerals, fiber, oligosaccharides, and other phytochemicals that are good for health. Sweet potato production is very abundant, but its utilization is not maximal yet. The purpose of this research was to produce sweet potato cream soup. The study was done by experimental method and organoleptic test by using Quantitative Descriptive Analysis (QDA) method and evaluation of the final product by using a hedonic method. The steps in this study include prescription cream soup analysis, focus group discussion (FGD), trial and evaluation with QDA method, the final product is tested receiving power by using hedonic test. The results showed cream of sweet potato soup has nutritional adequacy as a breakfast menu, has the characteristics of savory, shiny, sweet potato and spice. Cream of sweet potato soup is favored bay panels. Thus cream of sweet potato soup is perfect for a healthy breakfast.